THE IMPLEMENTATION OF WOMENPRENEUR MINDSET AND PROACTIVE PERSONALITY IN THE EFFORTS TO IMPROVE MSME PERFORMANCE - Prastiwi, Ni Luh Putu Eka Yudi; Hartawan, I Gusti Made Dharma; Kasih, Ni Luh Sri; Agustin, A. A. Ayu Mas Tanti; Sari, Putu Ratna Komala (International Journal of Application on Economics and Business, 2023)
This research seeks to examine the impact of the womenpreneur mindset and proactive personality on the performance of MSMEs. The study employed a quantitative approach through the administration of questionnaires to 50 women involved in MSMEs. Data analysis was carried out using SPSS 25.0. The findings of this research contribute to enhancing understanding in the realms of human resource management and entrepreneurship, particularly in relation to factors influencing MSME performance. According to the study, the womenpreneur mindset and proactive personality make significant contributions to enhancing the performance of MSMEs.